Sequence Analyses and Phenotypic Characterization Revealed Multidrug Resistant Gene Insertions in the Genomic Region Encompassing Phase 2 Flagellin Encoding fljAB Genes in Monophasic Variant Salmonella enterica Serovar 4,5,12:i:- Isolates From Various Sources in Thailand - Win, Aye Thida; Supa-amornkul, Sirirak; Orsi, Renato H.; Carey, Jaclyn H.; Wolfgang, William J.; Chaturongakul, Soraya (Frontiers in Microbiology, 2021)
Salmonella enterica serovar 4,5,12:i:- (S. 4,5,12:i:-), a monophasic variant of Salmonella Typhimurium (STm) lacking the phase 2 flagellin encoding genes fljAB, has become increasingly prevalent worldwide. The increasing trends in multidrug resistant (MDR) S. 4,5,12:i:- prevalence also pose an important global health threat. Though many reports have characterized phenotypic and genotypic drug resistance of this serovar, few studies have characterized antimicrobial resistance of this serovar in Thailand. In this study, 112 S. 4,5,12:i:- isolates from various sources in Thailand were screened using polymerase chain reaction (PCR) to detect the presence of five target regions which are associated with antimicrobial resistant (AMR) genes, in the genomic region that contained fljAB genes in STm. We determined AMR phenotypes of all isolates by Kirby-Bauer disk diffusion method. Whole genome sequencing (WGS) was performed on 53 representative isolates to characterize the genetic basis of AMR phenotype and to identify the location of AMR determinants. Based on PCR screening, nine PCR profiles showing distinct deletion patterns of the five target regions have been observed. Approximately 76% of isolates (or 85 of 112 isolates), all of which were Thai isolates, contained five target regions inserted between STM2759 and iroB gene. A total of 21 phenotypic AMR patterns were identified with the predominant AmpST R-Type (i.e., 84% [or 94 of 112] tested positive for resistance to ampicillin, streptomycin, and tetracycline), and 89% [or 100 of 112] were found to be MDR (defined here as resistant to at least three classes of tested antimicrobials). Using WGS data, a total of 24 genotypic AMR determinants belonging to seven different antimicrobial groups were found. AMR determinants (i.e., blaTEM-1, strB-A, sul2, and tetB, conferring resistance to ampicillin, streptomycin, sulfonamides, and tetracycline, respectively) were found to be inserted in a region typically occupied by the phase 2 flagellin encoding genes in STm. These resistant genes were flanked by a number of insertion sequences (IS), and co-localized with mercury tolerance genes. Our findings identify AMR genes, possibly associated with multiple IS26 copies, in the genetic region between STM2759 and iroB genes replacing phase 2 flagellin encoding fljAB genes in Thai S. 4,5,12:i:- isolates.